2017
DOI: 10.1002/ceat.201600709
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐Functionalized Graphene Oxide for Enhanced Permeability and Antifouling of Ultrafiltration Membranes

Abstract: Chitosan-functionalized graphene oxide (CS-GO) was synthesized and incorporated into a poly(vinylidene fluoride) (PVDF) ultrafiltration membrane. The effect of CS-GO addition on the morphology and membrane performance was studied through water contact angle, scanning electron microscopy, atomic force microscopy, porosity, pore size, and permeation measurements as well as rejection tests and antifouling experiments. The CS-GO/PVDF membrane exhibited higher water flux, bovine serum albumin (BSA) rejection rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 43 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…Mixed-matrix membranes or polymer-inorganic membranes are fabricated by adding nanoparticle additives into the polymer matrix [ 31 ]. Nanoparticles such as graphene oxide [ 12 , 32 , 33 , 34 , 35 ], silica [ 22 , 36 ], titanium dioxide [ 37 , 38 , 39 ], nanoclay [ 40 , 41 , 42 ], halloysite nanotubes [ 43 ], nanowires [ 44 ], and silver nanoparticles [ 45 ] had been used to embed in the polymeric matrix. For example, Wan Ikshan et al [ 43 ], synthesized halloysite nanotube-hydrous ferric dioxide through chemical precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed-matrix membranes or polymer-inorganic membranes are fabricated by adding nanoparticle additives into the polymer matrix [ 31 ]. Nanoparticles such as graphene oxide [ 12 , 32 , 33 , 34 , 35 ], silica [ 22 , 36 ], titanium dioxide [ 37 , 38 , 39 ], nanoclay [ 40 , 41 , 42 ], halloysite nanotubes [ 43 ], nanowires [ 44 ], and silver nanoparticles [ 45 ] had been used to embed in the polymeric matrix. For example, Wan Ikshan et al [ 43 ], synthesized halloysite nanotube-hydrous ferric dioxide through chemical precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of the PES/GNPs‐O membrane could be done by simple phase inversion method through immersion precipitation route making this method the most widely used for commercial membrane fabrication today. For instance, studies of the application of this membrane type have been conducted in water treatment , ethanol dehydration , or gas separation . However, understanding the properties and characters would promote the decision for its technological application in order to obtain an effective and efficient process.…”
Section: Resultsmentioning
confidence: 99%
“…The increased band at around 1610 cm −1 was due to C=C functional groups. However, no absorption bands corresponding to amino-functionalised GO were observed [23,29]. Furthermore, the reduced intensity of the band corresponding to C-Cl showed that this group participated in the covalent attachment of GO.…”
Section: Synthesis Of Ag Nps@go-fl-csmentioning
confidence: 97%